Schuman Report on Europe State of the Union 2011 - Chopin, Thierry; Foucher, Michel; Springlink (Paris Springer Paris Imprint: Springer, 2011)
The Schuman 2011 Report on the State of the Union is both a reference and a tool. A reference: bringing together contributions from leading specialists, including an interview with Herman Van Rompuy, President of the European Council. This Report proposes a novel analytical framework, so that everyone can form his/her opinion on a series of key questions: ?The European Union in the crisis: balance between national and European interests ?Ways out of the financial crisis ?The European Union, an actor in a changing world. A tool: with its thirty original colour maps it brings together essential information. ?The summary of political Europe: analysis of European elections 2010, calendar of the elections in 2011, political and economic representation of women in Europe, normative production of the Union in 2010, protection of Human Rights in 2010 ? Europe in Figures: a new series of statistics and maps, covering all major current issues (growth, purchasing power, economic policy, demography, immigration, energy, environment, globalization, European policies, ...). The key to understanding the European dynamic. Under the direction of T. Chopin and M. Foucher, the following people have contributed to this book: H. Van Rompuy, J. de Larosière, A-M. Idrac, A. Lamassoure, J. Bitterlich, P. Camus, W. Martens, J-D. Giuliani, A. Danjean, J-M. Daniel, J-P. Filiu, R. Beetsma, R. Gradus, P. Joannin, O. Dord, J-F. Jamet, M. Balent, M. Borchard, R. Freudenstein, C. Deloy, P-A. Molina, F. Lirzin, S. Paulo.
Electronic reproduction.
Keywords: European Union; European Union countries -- Statistics; European Union countries -- Economic conditions -- 21st century; European Union countries -- Politics and government -- 21st century; Electronic books